2012
DOI: 10.5588/ijtld.11.0148
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 5-year mortality in pulmonary <I>Mycobacterium avium-intracellulare</I> complex disease

Abstract: Patients with cavitary lesions require immediate treatment for sputum culture conversion and to improve their chances of survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
70
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 0 publications
4
70
1
Order By: Relevance
“…The 1-year mortality rate in our study (9%) was lower than that (25%) found in a previous study of macrolide-resistant MAC-LD (14), although the 5-year mortality rate was significantly higher (47%) in the present study. Moreover, the 5-year mortality rate in patients with macrolide-resistant MAC-LD in our study was much higher than those (13 to 26%) in patients with newly diagnosed MAC-LD in previous studies (35)(36)(37). These time-dependent increases in mortality indicate the difficulty of managing patients with macrolide-resistant MAC-LD.…”
Section: Discussioncontrasting
confidence: 51%
“…The 1-year mortality rate in our study (9%) was lower than that (25%) found in a previous study of macrolide-resistant MAC-LD (14), although the 5-year mortality rate was significantly higher (47%) in the present study. Moreover, the 5-year mortality rate in patients with macrolide-resistant MAC-LD in our study was much higher than those (13 to 26%) in patients with newly diagnosed MAC-LD in previous studies (35)(36)(37). These time-dependent increases in mortality indicate the difficulty of managing patients with macrolide-resistant MAC-LD.…”
Section: Discussioncontrasting
confidence: 51%
“…8,9 Mycobacteria have high genetic diversity, even within species, 31 and varying virulence could be part of this diversity. Tatano and colleagues 32 compared in vitro virulence of five strains of M avium isolates from patients with NB with fi ve strains isolated from patients with cavitary PNTM, a form of disease associated with higher mortality, 33 to determine whether diff erences in virulence correlated with diff erent patterns of disease. No signifi cant diff erences were found among any of the strains tested with respect to cellular internalization, replication within human type 2 alveolar cells and macrophages, or macrophage production of reactive nitrogen or oxygen species or susceptibility to either of these macrophage antimicrobial mechanisms.…”
Section: Iatrogenic Risk Factorsmentioning
confidence: 99%
“…Patients with fibrocavitary disease usually require immediate treatment because cavitary disease is associated with a higher rate of mortality due to NTM pulmonary disease [14,15].…”
mentioning
confidence: 99%
“…Initiation of NTM treatment should be individualized considering disease types, comorbid conditions, and age. Patients with fibrocavitary disease usually require immediate treatment because the presence of cavitary disease is associated with higher mortality rate [19,20]. A study demonstrated that clarithromycin and capreomycin have high antimicrobial activities against M. intracellulare isolates; clarithromycin and amikacin resistance could be more readily and rapidly detected using molecular scanning of corresponding drug target than conventional drug susceptibility testing.…”
mentioning
confidence: 99%